TRIANGULAR THEORY OF LOVE IN STEPHENIE MEYERS BREAKING DAWN: STRUCTURALISM APPROACH - ISWAHYUDI, RICKY (LANGUAGE HORIZON, 2018)
Breaking Dawn novel tells the story of the continuation from previous novel and with another problems that Bella has. Start with Bella?s decision to marry Edward and ended up having half human half vampire daughter. This thesis will analyse each component from triangular theory of love that being depicted in the novel using structuralism approach. There are three components of triangular theory of love. They are passion, intimacy, and commitment. It is best to analyze how triangular theory of love depicted in this novel using structuralism approach. How each character action in conscious way is constructed and depicted from three components triangular theory of love itself. Passion as one of the components from triangular theory of love put the study in to how people attracted to someone or something and there is always a reason for that. This component as one of the components in triangular theory of love represents in such an event before Bella and Edward?s wedding. Intimacy as one of the components from triangular theory of love put the study in to how people can show their closeness with someone that they loved. In Breaking Dawn novel, this thesis can analyze from such an event during Bella and Edward?s honeymoon in Isle Esme. Commitment as one of the components from triangular theory of love put the study in about how big a person love is for her beloved one. In Breaking Dawn novel, commitment component depicted during Bella and Edward?s wedding.